Vegetation changes attributable to refugees in Africa coincide with agricultural deforestation - Maystadt, Jean-François; Mueller, Valerie; Van Den Hoek, Jamon; van Weezel, Stijn (IOP Publishing, 2020)
The recent adoption of the Global Compact on Refugees formally recognizes not only the importance of supporting the nearly 26 million people who have sought asylum from conflict and persecution but also of easing the pressures on receiving areas and host countries. However, few countries may enforce the Compact out of concern over the economic or environmental repercussions of hosting refugees. We examine whether narratives of refugee-driven landscape change are empirically generalizable to continental Africa, which fosters 34% of all refugees. Estimates of the causal effects of the number of refugees—located in 493 camps distributed across 49 African countries—on vegetation from 2000 to 2016 are provided. Using a quasi-experimental design, we find refugees bear a small increase in vegetation condition while contributing to increased deforestation. Such a combination is mainly explained not by land clearance and massive biomass extraction but by agricultural expansion in refugee-hosting areas. A one percent increase in the number of refugees amplifies the transition from dominant forested areas to cropland by 1.4 percentage points. These findings suggest that changes in vegetation condition may ensue with the elevation of population-based constraints on food security.